Implementation of social media platform for increasing brand awareness of Tista tourism village - Paramita, Ratri; Zulfan , Muhammad (Journal of Commerce, Management, and Tourism Studies, 2024)
The aim of this research is (1) To find out how the management of the Tista tourism village promotes the brand of the village and (2) What the impact of the application of the social media platform on the awareness of the Tista village is. The Tista tourist village is an independent tourist village that started from the community, by the community, and for the community based on the spirit of mutual cooperation in building a village as well as shared commitment and the many potentials that exist in the area that we need to preserve and develop, therefore giving rise to an idea for form a tourism village. This tourism village aims to utilize existing human resources and natural resources so that the existence of Tista tourism village can be known and recognized by the wider community so that it can be attractive for tourists who just come to enjoy the rural atmosphere in our area. Data collection methods are observation, interview, documentation, and literature study. The analysis techniques used are descriptive and qualitative. The results of this study indicate that there are some social media platforms used for increasing brand awareness in the village and there is also improvement of the tourism activities arising from the social media. It can be recognized from the increasing number of viewers on the platform which at the meantime uses Facebook, Instagram, and  Tik-Tok.